Entropy generation optimisation for unsteady stagnation Casson nanofluid flow over a stretching sheet with binary chemical reaction and Arrhenius activation energy using the bivariate spectral quasi-linearisation method. Issue 1 (31st December 2022) - Oyelakin, I. S.; Mthethwa, H. Sithole; Kameswaran, Peri K.; Shaw, S.; Sibanda, P.
Abstract : The heat and mass transport with Arrhenius activation energy has countless uses such as in nuclear reactors, the synthesis of chemical compounds, geothermal artificial lakes, and retrieval of thermal lubricants. The focus of this work is the analysis of Arrhenius activation energy and binary chemical reaction in a stagnation point Casson nanofluid flow over a stretching sheet. The system is subjected to a nonlinear radiation and a magnetic field. The transport equations are simplified using the Williams and Rhyne non-similar transformation. The solution to the transformed coupled system of nonlinear partial differential equations is obtained using the bivariate spectral quasi-linearisation method. Entropy generation that measures the degenerate useful energy and deprivation of the performance of engineering systems is analysed. Numerical results describing changes in the fluid velocity, temperature, concentration, entropy generation and Bejan number are presented and discussed for different fluid parameters. Activation energy parameter boosts up the solute concentration at the surface while an opposite is observed far away from the surface. The entropy generation decreases with an increase in the unsteady parameter and Casson number, while the opposite response was observed for a higher Reynolds number. Brinkman number gears up the entropy generation while it shows an opposite phenomenon for Bejan number.